Purification and characterisation of the fission yeast Ndc80 complex - Matsuo, Yuzy (Protein Expr Purif, 2017)
The Ndc80 complex is a conserved outer kinetochore protein complex consisting of Ndc80 (Hec1), Nuf2, Spc24 and Spc25. This complex comprises a major, if not the sole, platform with which the plus ends of the spindle microtubules directly interact. In fission yeast, several studies indicate that multiple microtubule-associated proteins including the Dis1/chTOG microtubule polymerase and the Mal3/EB1 microtubule plus-end tracking protein directly or indirectly bind Ndc80, thereby ensuring stable kinetochore-microtubule attachment. However, the purification of the Ndc80 complex from this yeast has not been achieved, which hampers the in-depth investigation as to how the outer kinetochore attaches to the plus end of the spindle microtubule. Here we report the two-step purification of the fission yeast Ndc80 holo complex from bacteria. First, we purified separately two sub-complexes consisting of Ndc80-Nuf2 and Spc24-Spc25. Then, these two sub-complexes were mixed and applied to size-exclusion chromatography. The reconstituted Ndc80 holo complex is composed of four subunits with equal stoichiometry. The complex possesses microtubule-binding activity, and Total Internal Reflection Fluorescence (TIRF)-microscopy assays show that the complex binds the microtubule lattice. Interestingly, unlike the human complex, the fission yeast complex does not track depolymerising microtubule ends. Further analysis shows that under physiological ionic conditions, the Ndc80 holo complex does not detectably bind Dis1, but instead it interacts with Mal3/EB1, by which the Ndc80 complex tracks the growing microtubule plus end. This result substantiates the notion that the Ndc80 complex plays a crucial role in establishment of the dynamic kinetochore-microtubule interface by cooperating with chTOG and EB1.